Hubungan Kepatuhan Diet, Aktivitas Fisik, dan Dukungan Keluarga dengan Kadar Glukosa Darah pada Pasien Diabetes Melitus - Khulwatunnisa Khulwatunnisa; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (NAJ Nursing Applied Journal, 2025)
Diabetes mellitus triggers complications that can cause nerve damage, kidney damage, vision problems, diabetic wounds and cardiovascular problems. Healthy eating patterns, exercise, and family support are several strategies for controlling diabetes mellitus and maintaining blood sugar levels in diabetes sufferers within normal limits. The aim of this study was to determine the relationship between blood glucose levels in individuals with diabetes mellitus and diet compliance, physical activity and family support. Purposive sampling, cross-sectional techniques, and analytical observation were used in this study, which involved 119 participants. Based on this research, there was good family support (84.9%), moderate physical activity (63.9%), and high dietary compliance (84.9%). Analysis using the chi square test obtained a p value of 0.001 (<0.05) which shows that there is a significant relationship between diet compliance, physical activity and family support with blood glucose levels in diabetes mellitus patients at the Bangetayu Health Center, Semarang.